Notes on Early Land Plants Today. 68. Miscellaneous notes on Marchantiophyta - Söderström, Lars; Vana, Jiri; Crandall-Stotler, Barbara; Renner, Matt; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2015)
During work with the forthcoming world checklist of hornworts and liverworts (Söderström et al., in press) a number of nomenclatural problems have been detected and most have been dealt with in the series “Notes on Early Land Plants Today” published in Phytotaxa. However, some more corrections are needed. They are dealt with here.